Refractive and Visual Outcomes After Bilateral Implantation of a Trifocal Intraocular Lens in a Large Population - Carreño E (Dove Medical Press, 2020)
Edgardo Carreño,1 Edgardo A Carreño,1 Rodrigo Carreño,1 Maricarmen Carreño,1 Veronica López,1 Richard Potvin2 1Centro Oftalmológico Carreño, Las Condes, Santiago, Chile; 2Science in Vision, Akron, NY, USACorrespondence: Richard PotvinScience in Vision, 6197 Dye Road, Akron, NY 14001, USAEmail rick@scienceinvision.comPurpose: To review refractive, visual acuity, defocus curve and contrast sensitivity results after bilateral implantation of a trifocal intraocular lens (IOL) in a large population.Setting: One site in Santiago, Chile.Design: Single arm, non-randomized retrospective chart review.Methods: This was a single-arm retrospective chart review of clinical outcomes after bilateral implantation of a trifocal IOL (Panoptix®), both toric and non-toric versions. Binocular visual acuity at 4 m, 60 cm and 40 cm was tested. Other tests included refraction, mesopic and photopic contrast sensitivity, and defocus curve measurement.Results: The review included 500 eyes of 250 patients implanted with the trifocal IOL and 200 eyes of 100 patients implanted with the trifocal toric IOL, with no clinically significant differences between groups. Ninety-six percent of all eyes were within 0.50D of the intended spherical equivalent correction. In the toric group, 94% of eyes (187/200) had a residual refractive cylinder ≤ 0.50D, compared to 81% of eyes (406/500) in the non-toric group. Four out of five patients (80.6%, 282/350) had a binocular uncorrected VA of 0.1 logMAR (20/25) at all test distances. Mean defocus was 0.1 logMAR or better from vergences from 0.00 to − 3.00 D (corresponding to vision from distance to about 33 cm). With a cutoff of 0.2 logMAR, 96% of patients had a range of vision 2.5 D or greater. Contrast sensitivity was similar between the toric and non-toric lenses, and similar to age-matched normal results.Conclusion: The non-toric and toric trifocal IOLs provided good distance, intermediate and near vision to patients, with a wide range of vision and good contrast sensitivity.Keywords: trifocal IOL, contrast sensitivity, toric trifocal IOL